Człowiek: podmiot wychowania czy jego funkcja - Kiereś, Barbara (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article discusses the problem of the subjectivity of man as the purpose of education. This problem is put in context of a dispute between the tradition of realism and idealism about the understanding of man and his subjectivity (causative). There are two trends within idealism – individualism and collectivism, and in the confrontation with them, pedagogical personalism. It is proven that the tradition of idealism is embedded in cognitive reductionism, which is determined by the erroneous concept of philosophy. It is shown that the tradition of realism and the understanding of subjectivity developed on its basis reach back to the thought of ancient Greek, and its development and justification is the contribution of Christian culture.